Clinical role of brexpiprazole in depression and schizophrenia - Parikh NB; Robinson DM; Clayton AH (Dove Medical Press, 2017)
Nishant B Parikh, Diana M Robinson, Anita H Clayton Psychiatry and Neurobehavioral Sciences, University of Virginia School of Medicine, Charlottesville, VA, USA Abstract: Brexpiprazole, a serotonin–dopamine activity modulator, is the second D2 partial agonist to come to market and has been approved for the treatment of schizophrenia and as an adjunctive treatment in major depressive disorder. With less intrinsic activity than aripiprazole at the D2 receptor and higher potency at 5-HT2A, 5-HT1A, and α1B receptors, the pharmacological properties of brexpiprazole suggest a more tolerable side effect profile with regard to akathisia, extrapyramidal dysfunction, and sedation. While no head-to-head data are currently available, double-blind placebo-controlled studies show favorable results, with the number needed to treat (NNT) vs placebo of 6–15 for response in acute schizophrenia treatment and 4 for maintenance. NNT is 12 for response and 17–31 for remission vs placebo in major depression. In schizophrenia trials, treatment-emergent adverse effects (TEAEs) and discontinuation rates due to TEAEs were lower in treatment groups vs placebo (7.1%–9.2% vs 14.7%, respectively). Meanwhile, discontinuation rates due to TEAEs in depression studies were higher in treatment groups vs placebo (1.3%–3.5% vs 0–1.4%, respectively) and appeared dose dependent. Rates of akathisia are lower compared to those with aripiprazole and cariprazine, weight gain is more prominent than with aripiprazole, cariprazine, or ziprasidone, and sedation is less than with aripiprazole but more than with cariprazine. Brexpiprazole target dosing is 2–4 mg in schizophrenia and 2 mg in depression augmentation. Dose adjustments should be considered in hepatic or renal dysfunction and/or in poor cytochrome P450 2D6 metabolizers. While brexpiprazole represents an exciting second entry for D2 partial agonists with positive studies thus far, direct head-to-head comparisons will shed more light on the efficacy and side effect profile of brexpiprazole. Keywords: serotonin–dopamine activity modulator, antipsychotic, partial agonist, psychopharmacology